The use of hydroflouric acid as a surface treatment material on bond strength in cohesive fractures of fused to metal porcelain restoration - Andri Sinulingga; Putri Welda Utami Ritonga; Syafrinani (Indonesia Prosthodontic Association, 2023)
Background : Porcelain fused to metal (PFM) restoration is one of the most common restorations for fixed dentures because of its high strength, durability, biocompatibility, and satisfactory esthetics. The brittle nature of ceramic makes it easily fractured. Porcelain fracture is the second largest failure after caries. Repairing porcelain directly using composite resin becomes an option because it is cost-effective and easy to apply. The repair process requires chemical and mechanical bonding to create a strong resin bond. Hydrofluoric acid (HF) can be used as a surface treatment material to achieve good bonding. Concentration and etching time affect the bond strength. However, HF becomes harmful when in contact with soft tissues. Strict protocols in its application are observed and prolonged use in the mouth is avoided. Objective: To describe the effect of HF as a surface treatment material on bonding strength between porcelain and composite resin. Knowing the HF bonding strength changes to time and concentration as a surface treatment material for direct repair. Conclusion : Minimizing the contact of HF on soft tissues, applying HF in the mouth for a short time without reducing its function to achieve good bonding strength. Keywords : porcelain fused to metal, surface treatment, hydrofluoric acid